Randomised Trial: Adrenaline & Dexamethasone Vs. Adrenaline In Children With Bronchiolitis - Sidra Choudhary; Israr Liaqat; Sidra Tul Muntaha; Rafiq Ahmad; Jawad Niazi; Mian Mansoor (Journal of Rawalpindi Medical College, 2024)
Objective: To compare treatment outcomes with adrenaline and dexamethasone versus adrenaline alone in children with bronchiolitis.